Analysis of Student’s Mathematical Communication Ability Using Digital LKPD with RME (Realistic Mathematics Education) Approach - Oktania Putri, Mardhotillah; Novika Sukmaningthias (JTMT: Journal Tadris Matematika, 2025)
This research is motivated by the low mathematical communication skills of students which is one of the main problems in learning mathematics in schools. One of the causes is the lack of innovation in learning tools that can link mathematical concepts with students' daily life experiences. This study aims to describe the mathematical communication skills of students through the use of Digital Learner Worksheets (LKPD) based on the Realistic Mathematics Education (RME) approach. This type of research is descriptive research conducted at SMP Negeri 45 Palembang in the 2024/2025 school year. The research sample consisted of class VIII.3 which amounted to 25 students. The research instruments were three essay questions to measure mathematical communication skills and semi-structured interviews. The data were analyzed using an assessment rubric and categorized into three levels of mathematical communication ability, namely high, medium, and low. The results showed that there were 6 students with high mathematical communication ability, 10 students with medium mathematical communication ability, and 9 students with low mathematical communication ability. The conclusion of this study confirms that the RME approach in Digital LKPD can support learners in expressing mathematical ideas more realistically and relevant to everyday life.